Sustainable Asphalt Concrete for Road Construction and Building Material. Issue 1 (June 2021) - Abuaddous, M; Dahim, M; Ismail, R; Taamneh, M; Alomari, A H; Darwish, W; Al-Mattarneh, H
Abstract: In this study, the possibility of producing new geopolymer concrete from olive oil waste in Jordan is presented. Olive oil residues in Jordan and many Mediterranean countries constitute a major environmental and health problem. So far, the waste is disposed of by means of sanitary landfill, and this poses an environmental risk and pollutes the groundwater, the main source of water in Jordan. The ash remaining from burning olive oil residues was used to produce geopolymer concrete by adding sodium hydroxide and without using any Portland cement. Mixtures were prepared using the central composite design. The focus was on the two most important factors affecting the properties of geopolymer concrete, which is the amount of ash and the amount of alkaline solution. After curing the concrete and passing 28 days, the compressive strength, slump, absorption, and porosity were measured. The Results of compressive strength, absorption and porosity was excellent in comparison with the results obtained from conventional concrete. Despite the promising results the slump of the proposed concrete is low, and the slump loss was very fast. Further studies are needed to improve the workability of geopolymer concrete from olive oil waste. This concrete allows to recycle a large amount of olive waste in Jordan and many other countries which reduce the impact on health and environment.